Integrasi Isu Energi Terbarukan dalam Pembelajaran Perubahan Energi untuk Meningkatkan Literasi Lingkungan: Tinjauan Literatur - Elia Putri; Hanna Aulia Siregar; Dahlia Harahap; Halimah Berliani; M. Za'far Tholib; R.R Misha Emyra; Riska Pradila (Universitas Garut, 2026)
Global environmental crises, including global warming and climate change, demand a radical reorientation in science education to foster ecological awareness. This study aims to examine the integration of renewable energy issues within the